Environmental Vulnerability of the Caravelas (BA) Coastal Plain as Subsidy to Environmental Planning - Souza, Sírius Oliveira; Vale, Cláudia (Sociedade & Natureza, 2016)
The use pressure on coastal zones and their effects on the equilibrium of ecosystems have been a subject often discussed in the scientific literature. This situation takesthe planners to look for summarize the scientific information to develop models of integrated coastal studies. From these studies, this paper aims to analyze the environmental vulnerability of the Caravelas Coastal Plain in the state of Bahia (Brazil) by means of geoprocessing techniques in a Geographic Information System, with the purpose of subsidize the environmental planning.Lastly, this research has generated environmental vulnerability levels as from the integration of geological, soil conditions, slope and use and occupation of land characteristics. The classes that have high and very high vulnerability include mangroves, the floodplains and shoreline. In the class that has an average environmental vulnerability is included areas of the coastal plain and the slopes of the trays.The classes of low and very low vulnerability include the trays located at the northwest portion of the study area. The results obtained allowed understand the different degrees of vulnerability of each unit front of some human pressures, can be used as a tool for local and regional environmental planning.